A clinicopathologic evaluation of 230 cases of mature cystic teratomas - Sherpa, Palzum; Baral, Reetu (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: Mature cystic teratomas, commonly known as dermoid cyst, is the most common benign tumor of ovary. The aim of this study was to evaluate the clinicopathologic behavior of mature cystic teratomas. Methods: A retrospective cross sectional study on a series of cases was performed in the Department of Pathology, Patan Academy of Health Sciences, Patan Hospital, Lalitpur, Nepal from April 2011 to March 2016. Data from the histopathology database were analyzed using SPSS version 16.0. Results: MCT comprised 230 (57.6%) out of total 399 cases of ovarian neoplasms. The age range of the patients was 8-74 years. The sizes of the tumors ranged from 2.5-20cm. 12% of the cases were bilateral. Ischemic modifications, presumably due to torsion, were noted in 10% of the cases, mostly in tumors larger than 10cm. None of the tumors of less than 5cm presented with signs of torsion. Malignant transformation was present in seven (3%) cases and was seen especially in older patients and in larger tumors. Squamous cell carcinoma was the most common malignant tumor seen in five cases. One case was a mixed germ cell tumor with components of MCT and yolk sac tumor. Conclusions: MCT is the most common germ cell tumor in patients of the reproductive age group. Complications such as torsion and malignant transformation occur mostly in larger tumors.